AN NUMERICAL METHOD BASED ITERATIVE PROCESS TO CHARACTERIZE MICROWAVE PLANAR CIRCUITS - Tellache, Mohamed; Lamhene, Youcef; Haraoubia, Brahim; Baudrand, Henri (International Journal of Computing, 2014)
In the present work, the modeling of microwaves planar circuits is proposed with an original method based on the Waves Concept Iterative Process (WCIP). It consists in the development of simulation software based on an iterative method. The iterative method is developed from the fast modal transform on a two-dimensional fast Fourier transform (FFT) algorithm. The method has been applied to the characterization and the modeling of patch antennas with notches in microstrip and coplanar technology and the quarter wavelength directive coupler. The obtained results are very powerful and successfully compared to others methods in term of time and reliability of convergence and particularly the accuracy of the results obtained in comparison with previous works.